Auctis finibus populi Romani? Les raisons de l’extension du pomerium sous le principat - Lyasse, Emmanuel (Gerión. Revista de Historia Antigua, 2005)
An examination of the material in total, and in particular of the so-called Lex de imperio Vespasiani shows that the relationship between the extension of the pomerium and the extension of the Empire is far from being clear. This matter seems to have been obscure even for the people of that. This invites a reconsideration of the question of an extension of the pomerium by Augustus, an interpretation which has been generally discounted over the past few years.